“Mal del ciprés”: búsqueda de la causa más probable de daño mediante un análisis deductivo y comparativo = “Cypress Mortality”: search the more probably damage cause by means of deductive and comparative analysis - El Mujtar, Veronica Andrea; Andenmatten, Ernesto (Facultad de Ciencias Forestales y Recursos Naturales, Universidad Austral de Chile, 2023)
The “cypress mortality” (“mal del ciprés”) is a disease of unknown causes, which affects cordillera cypress (Austrocedrus chilensis) in Argentina. In this work a basic guide to diagnosing plant diseases and to compare the cypress mortality with other forest diseases is shown for its application, in order to identify the most probable cause of damage. The systematic management of the information permitted to establish that the dates are not sufficient to discriminate between different damage agents. The association between the cypress mortality and others forest diseases allowed us to verify that there are several difficulties to diagnose and manage this pathologies. We detected several key points of the disease that should be considered in future investigations: absence of specific symptoms, absence of signs, subjective assignment of the degree of defoliation and the associated sanitary state, absence of an analysis model for disturbance.